Respon Pertumbuhan Seedling Anggrek Dendrobium Gradita 31 Pada Beberapa Kombinasi Media Ms dan Ekstrak Taoge - Dwi Dhita Apriyani; Yeni Yeni; Wika Anrya Darma; Lisa Erfa (Politeknik Negeri Lampung, 2026)
Problems in orchid development are still quite limited due to the lack of availability of uniform seeds and the slow growth process of orchids, resulting in limited availability of orchid plant seeds. Subculture is the transfer of plants by in vitro culture from old media to new media with a specific purpose. One type of organic PGR used is bean sprout extract which contains auxin and cytokinin for the growth of plant seedlings. The objectives of this study are, (1) To obtain the best concentration of MS media at the growth stage of Dendrobium